Top down or bottom up? A cross-national study of vertical occupational sex segregation in twelve European countries - Andrea Schäfer; Ingrid Tucci; Karin Gottschall (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Starting with a comparative assessment of different welfare regimes and political economies from the perspective of gender awareness and pro-women policies, this paper identifies the determinants of cross-national variation in women's chances of being in a high-status occupation in twelve West European countries. Special emphasis is given to size and structure of the service sector, including share of women in public employment and structural factors such as trade union density and employment protection. The first level of comparison between men and women concentrates on gender representation in the higher echelons of the job hierarchy, while in the second section we extend the scope of analysis, comparing women in high-status occupations and low-wage employment in order to allow for a more nuanced study of gender and class interaction. The first analysis is based on European Social Survey data for the years 2002, 2004, 2006, and 2008, capturing recent trends in occupational dynamics. Results indicate that in general a large service sector and a high trade union density enhance women's chances of being in high-status occupations while more specifically a large public sector helps to reduce channeling women into low-wage employment. Thus, equality at the top can well be paired with inequality at the bottom, as postindustrial countries with a highly polarized occupational hierarchy such as the UK show.
Keywords: P5; D6; J2; 330; occupational sex segregation; gender equality; public sector employment; cross-national comparison